Prospects of domestic container ports in Asia : a case study on Vietnam - Xu, Shen Yi (2015)
There are precious few reports on how the Cascade Effect relates to the economic background of intra-Asia trade. By looking at ports in Vietnam, this report shows how the Cascade Effect, the economic background of intra-Asia sea trade, the economy of Vietnam and the ports of Vietnam interact. In doing so this report speculates the prospects of Vietnam ports. Research had been conducted through interviews. This report focuses on the ports in North and South of Vietnam, namely Hai Phong Port, Cai Lan Port and Lach Huyen International Port in the North, and ports in Ho Ch Minh City area and ports in Cai-Mep-Thi Vai area in the South. In general ports in Vietnam have the infrastructure to accommodate vessels cascaded down, although exceptions do exist. However, operations remain untested. Factors such as port users’ mentalities, hinterland condition further complicates the issue. The prospects are not bad, although ports are recommended to develop in different directions. The key limitation in this research lays in the lack of suitable interviewees. This report has implications on how the Cascade Effect affects ports serving intra-Asia container feeder trade.